Analisis Perbandingan Migrasi Listrik Pascabayar Menjadi Prabayar Terhadap Pendapatan PT. PLN (Persero) ULP Binjai Timur - Sitompul, Imelda; Syafina, Laylan; -, Kusmilawaty (Indonesian Journal of Islamic Economics and Business, 2023)
The purpose of this study is to analyze the comparison of PT PLN (Persero)'s income using postpaid electricity services and after migrating to prepaid in the East Binjai region. This study uses descriptive qualitative research using numbers and descriptive analysis based on income data for 2021 to 2022. The results show that postpaid electricity income is greater than prepaid electricity income. A comparison of postpaid and prepaid electricity revenue in 2021 to 2022 will get a difference of 81%: 19%. This difference indicates that consumers of PT PLN (Persero) ULP Binjai Timur still use postpaid services a lot, this is because most consumers are from households who are still not educated regarding the use of prepaid kwh. These results make PT PLN (Persero) ULP Binjai Timur more active in promoting prepaid services so that consumers in the East Binjai region migrate to prepaid and increase income without receivables from consumers.